UCP2 866 G/A gene (rs659366) polymorphism associated with diabetes type 2 in Turkish population - Gozel, Nevzat; Dalkilic, Semih (Mattioli 1885, 2017)
Type 2 diabetes mellitus (T2DM) is a major health problem in worldwide and uncoupling protein-2 (UCP2) that have a role in the regulation of insulin secretion and emergence of diabetes mellitus. In this study we have investigate whether an association between UCP2 866 G/A polymorphism and T2DM. In this study we have collected peripheral blood samples from 50 type 2 diabetes mellitus patients and 50 healhty control individuals. Genomic DNA was isolated from blood samples and UCP2 866 G/A polymorphism was investigated by polymerase chain reaction restriction fragment lenght polymorphism assay (PCR-RFLP). In our results we have not observed any statistically significant association between UCP2 866 G/A polymorphism and risk of T2DM.
Keywords: diabetes mellitus type 2; UCP2 gene; polymorphism